2015
DOI: 10.1155/2015/850132
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Risk Behaviors and HIV Infection among Men Who Have Sex with Men and Women in China: Evidence from a Systematic Review and Meta-Analysis

Abstract: Objectives. To understand the current risk of HIV infection and transmission and further elucidate the underlying risk factors among men who have sex with men and women (MSMW) in China. Methods. Following PRISMA guidelines, we conducted a systematic review and meta-analysis of searching through Chinese and English available literature databases between January 2000 and June 2014 to identify articles. Results. Thirty-six articles (including 19,730 MSMW and 53,536 MSMO) met the selection criteria and the aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…Studies show that men's sexual proclivities have been responsible for the increased vulnerability to HIV. e data support the assertion that bisexual men and MSM individuals are more likely to acquire HIV than heterosexual men [7][8][9].…”
Section: Introductionsupporting
confidence: 70%
“…Studies show that men's sexual proclivities have been responsible for the increased vulnerability to HIV. e data support the assertion that bisexual men and MSM individuals are more likely to acquire HIV than heterosexual men [7][8][9].…”
Section: Introductionsupporting
confidence: 70%
“…Thus, in the final model, more experiences of sexual violence in the past 12 months were independently associated with not living with a spouse or steady partner, having a history of childhood sexual abuse, more adult experiences of homophobia, and higher scores on depression and hostility symptoms (see Table 2). Since previous research has shown differences between MSM and men who have sex with men and women (MSMW) in terms of sexual violence and other psychosocial factors (Davis et al, 2015; Dyer, Regan, Pacek, Acheampong, & Khan, 2015; Wang et al, 2015), we re-ran the hierarchical regression model excluding 48 participants who reported sex with women in the past two months. The substantive findings were mostly unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…Also, studies in LMIC have identified key differences between MSM and MSMW. It has been shown that MSMW have greater risk of intimate partner violence (Davis et al, 2015), higher HIV prevalence, greater likelihood of trading sex, greater use of alcohol and illicit drugs (Wang et al, 2015), lower odds of prior HIV testing (Bowring, Veronese, Doyle, Stoove, & Hellard, 2016), and more inconsistent use of condoms with male partners (Ramakrishnan et al, 2015) compared to MSM only. Accordingly, future studies should examine correlates of sexual violence victimization in separate models for MSM and MSMW.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that 31.2% of the 28,739 MSM in China had ever had sex with a woman [13]. Men who have sex with men and women (MSMW) are less likely to be infected with HIV than MSM-only (MSMO), probably because MSMW are more likely to practice insertive anal (with a man) and virginal intercourse with a woman, which is associated with lower HIV risk compared to receptive anal intercourse with a man [12, 1416]. On the other hand, MSMW are shown not to use condom consistently with female sexual partners [17], which may bridge HIV/STIs to their average-risk female sexual partners [18].…”
Section: Introductionmentioning
confidence: 99%